Economic Impact of Covid-19 And Revival Measures: Way Forward for South Asian Countries - FATIMA, SHAHEEN; AHMAD, AQEEL; MUMTAZ, RASHID; FATIMA, SAMREEN (The journal of contemporary issues in business and government, 2021)
COVID-19 has been declared and proven as a source of continuing global economic loss and world shattering over the last 100 years. This dilemma has encouraged global economy to run slow when international flights were shutdown, universities were closed, complete lockdown, ban on tourism and so on. This study aims at investigating economic perspective of Covid-19 on south Asian countries and revival measures adopted by them. Data was collected from already published research articles from various databases. By having a systematic review of latest related articles available online it is concluded that Covid-19 pandemic has severely affected nations globally. Factors responsible for such severe economic crisis are termination of daily wages jobs, labor immobility in lockdown, decline in production level, supply chain discontinuation, decline in exports, foreign direct investment, projects etc. Several measures were also suggested in light of literature to mitigate the economic impact. Implication of this study is useful in developing strategies and policies so as to combat the severe intensity of economic crisis on South Asian economies.